KEY CHALLENGES IN HUMAN RESOURCE EDUCATION WITHIN THE ENGINEERING DISCIPLINE DURING THE FOURTH INDUSTRIAL REVOLUTION - Fatemeh khakzad; Farid Ahmadi; Saeed JafarZadeh Ghooshchi (آموزش مهندسی ایران, 2025)
The Fourth Industrial Revolution is a complex phenomenon characterized by rapid technological changes that significantly transform social and economic landscapes, particularly in the workplaces. This transformation creates a gap between university curricula and the skill sets needed in the job market. If educational institutions do not adapt, they risk obsolescence, making effective curriculum revision essential. This study investigates the impact of the Fourth Industrial Revolution on education in engineering, focusing on its implications for human resource training. The Fuzzy SWARA approach was employed to assess the severity, likelihood, and detectability of educational challenges, while the Fuzzy ARAS method prioritized these issues. Key challenges identified include weaknesses in instructional content development and university incompatibility, which require immediate attention. The proposed model’s effectiveness was compared to the FMEA method, demonstrating its superiority. Strategies to address these challenges include enhancing curriculum quality, promoting exchange programs with leading universities, and fostering local technology manufacturing. The findings aim to improve methods for bridging the skills gap, ensuring students acquire the necessary skills for their current and future roles.